Fabrication of complex-shaped hydrogels by diffusion controlled gelation of nanocellulose crystallites. Issue 40 (3rd October 2017) - Maestri, C. A.; Bettotti, P.; Scarpa, M.
Abstract : Ca 2+ induced external and inverse ionotropic gelation of crystallites of nanocellulose allows the fabrication of small hydrogels with various morphologies using a reaction-diffusion driven process. Abstract : In this study we investigated the fabrication of small hydrogel objects by the coordination-driven assembly of supramolecular rod-like crystallites of nanocellulose, using ionotropic gelation as a methodological approach and Ca 2+ as a gelling agent. We proved that the gelation process is diffusion-mediated and fitting the equations modelling this process to the profile of the Ca 2+ front, a Ca 2+ diffusion coefficient in the incipient hydrogel of (4.5 ± 1.1) × 10 −6 cm 2 s −1 was calculated. At the steady-state a spatially homogeneous distribution of Ca 2+ -crosslinked sites in the hydrogel network was observed. External ionotropic gelation produced beads, wires or disks, while core–shell capsules were obtained by inverse ionotropic gelation. We demonstrated that equilibrium and dynamics of the distribution of Ca 2+ offer the opportunity to design precisely the size and shape of these small hydrogel objects. In particular, the core size and the shell thickness of the capsules can be tailored under kinetic controlled conditions. The proposed approach, with supramolecular structures of the natural source as assembling components and the water-in-water fabrication process, is fast, simple, and requires only sustainable chemistry and is easily implementable in automatic microfluidic platforms.